The results of molecular genetic testing for RET proto-oncogene mutations in patients with medullary thyroid carcinoma in a referral center after the two decade period - Rovcanin, B (Hippokratia, 2016)
Background: Medullary thyroid carcinoma (MTC) is a type of thyroid neoplasm which originates from parafollicular cells, and it is commonly diagnosed by calcitonin screening. Besides the sporadic form, the heritable form of MTC is characterized by constitutive activation of the RET (REarranged during Transfection) proto-oncogene caused by different mutations. Method: We collected data regarding RET genetic screening performed in the Center for Endocrine Surgery in Belgrade during a 20-year-period. The study group included 249 MTC patients who were genetically tested for RET mutations by Sanger’s sequencing method. Results: Genetic screening of the study population revealed nine different mutations of the RET gene in 42 carriers. The most common mutation was C634F, and it has been detected in 31 % (13/42) of individuals, while C618R, L790F, and S904S were present in only 2 % (1/42) each in the study group. Detected mutations were unequally distributed in different RET gene exons. Among MTC patients, 67 % (28/42) had mutation harbored in exon 11, while the rarest mutation was located in exons 10 and 15, each present in only 2 % (1/42) of patients. Conclusions: The RET gene mutation profile has a unique distribution in this study population when compared with the other European populations. The mutations in codon 634 are most common; therefore the cost-reducing genetic screening should primarily target this codon, and if the negative outcome appears, then other codons should be examined in the order that depends on their occurrence. Hippokratia 2016, 20(3): 187-191.